The Use of Cohesive Devices to Provide Coherence in Argumentative Essays of Universitas Negeri Semarang Graduate Students - Alfitri, Bahya; Yuliasri, Issy (Universitas Negeri Semarang, 2021)
This study aims to analyze the use of cohesive devices and the chain interaction of cohesive devices to achieve coherence in argumentative essays of Universitas Negeri Semarang graduate students. This study employed descriptive qualitative research design. It focused on cohesion and coherence analysis of students’ writing. The findings of the study showed that all of the types of cohesive devices such as reference, substitution, ellipsis, and reiteration were found in the students’ essays. These cohesive devices provide the coherence of the text through their semantic relation or bound which create the two cohesive chains; identity chains and similarity chains. The interaction between both chains can give explicit signals to guide readers towards the intended interpretation of the text. The result of this chain interaction is known as cohesive harmony. Most of students’ essays achieve coherence because the total tokens of the students’ essays enter more than 50% of chain interaction. Unfortunately, the students overuse certain types of cohesive devices such as repetition in creating the chains.